Efficient hepatic differentiation of hydrogel microsphere-encapsulated human pluripotent stem cells for engineering prevascularized liver tissue. (1st January 2023) - Deng, Shuai; Zhao, Xiaoyu; Zhu, Yanlun; Tang, Ning; Wang, Rongliang; Zhang, Xuerao; Qu, Fuyang; Ho, Yi-Ping; Lee, Wayne Yuk-Wai; Chen, Jiansu; Li, Mingqiang; Tao, Yu; et al.
Abstract: Liver tissue engineering is promising as an alternative strategy to treat liver failure. However, generating functional hepatocytes from stem cells is conventionally restricted by the immature status of differentiated cells. Besides, embedding hepatocytes in bulk scaffold is limited by a lack of vascularity and low cell-packing density. Here, we fabricate collagen type I (COL1) microspheres for efficient hepatic differentiation of pluripotent stem cells and subsequent assembly of prevascularized liver tissue (PLT). Using a microfluidic platform, we demonstrate that hydrogel COL1 microspheres (mCOL1) encapsulating human embryonic stem cells (hESCs) can be reproducibly generated and efficiently differentiated into hepatocyte-like cells (HLCs) microspheres for the first time. Compared with other culture configurations such as encapsulation of hESC in a bulk COL1 hydrogel and 2D monolayer culture, mCOL1 with high uniformity produce HLC microspheres of improved maturity based on comprehensive analyses of cell morphology, transcriptome profile, hepatic marker expression and hepatic functions. In addition, these HLC microspheres can be applied as building blocks to self-assemble with endothelial cells to construct a dense PLT. The PLT resembles native liver tissue with high cell-packing density, shows successful engraftment in mice liver following implantation, and exhibits improved hepatic function in vivo . Overall, it is believed that this multiscale technology will advance the fabrication of stem cell-based liver tissue for regenerative medicine, drug screening, and in vitro liver modeling.